2005
DOI: 10.1016/j.immuni.2004.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Recognition following Vγ9Vδ2 T Cell Receptor Interactions with a Surface F1-ATPase-Related Structure and Apolipoprotein A-I

Abstract: Vgamma9Vdelta2 T lymphocytes, a major gammadelta T lymphocyte subset in humans, display cytolytic activity against various tumor cells upon recognition of yet uncharacterized structures. Here, we show that an entity related to the mitochondrial F1-ATPase is expressed on tumor cell surface and promotes tumor recognition by Vgamma9Vdelta2 T cells. When immobilized, purified F1-ATPase induces selective activation of this lymphocyte subset. The Vgamma9Vdelta2 T cell receptors (TCR) and the F1-ATPase also bind a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
203
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(223 citation statements)
references
References 37 publications
6
203
2
1
Order By: Relevance
“…73 Recent developments in regards to alternative potential endogenous stress-induced ligands for Vc9Vd2 T cells provide new venues that may reveal how these cellular short-lived substrates can be potentially stabilized and presented extracellularly to the stress surveillance capabilities inherent in these lymphocytes. Scotet and colleagues 74 first reported that tumor recognition by Vc9Vd2 T cells could be mediated by the ectopic expression of ATP synthase/F1-ATPase, which is normally expressed on the internal membrane of mitochondria, and this interaction was enhanced by the cobinding of apolipoprotein A-I that is usually present in serum. Literally along the same vein, it was later observed that shear stress experienced by endothelial cells also led to the translocation of the ATP synthase b chain to the cell surface which resulted in the binding and activation of Vc9Vd2 T cells.…”
Section: Vd2 T Cells: To Know the Complex Burden Of Being Humanmentioning
confidence: 99%
“…73 Recent developments in regards to alternative potential endogenous stress-induced ligands for Vc9Vd2 T cells provide new venues that may reveal how these cellular short-lived substrates can be potentially stabilized and presented extracellularly to the stress surveillance capabilities inherent in these lymphocytes. Scotet and colleagues 74 first reported that tumor recognition by Vc9Vd2 T cells could be mediated by the ectopic expression of ATP synthase/F1-ATPase, which is normally expressed on the internal membrane of mitochondria, and this interaction was enhanced by the cobinding of apolipoprotein A-I that is usually present in serum. Literally along the same vein, it was later observed that shear stress experienced by endothelial cells also led to the translocation of the ATP synthase b chain to the cell surface which resulted in the binding and activation of Vc9Vd2 T cells.…”
Section: Vd2 T Cells: To Know the Complex Burden Of Being Humanmentioning
confidence: 99%
“…Aminobisphosphonate such as zoledronate may activate Vg9Vd2 T cells indirectly by blocking the mevalonate pathway and consequently promoting intracellular accumulation of isopentenyl pyrophosphate [8]. Recent findings suggest that the mitochondrial F1-ATPase exposed at the surface of the stimulating cells could participate to phosphoantigen presentation and subsequent Vg9Vd2 T-cell activation [12,13]. We and others have described that the synthetic phosphoantigen bromohydrin pyrophosphate (BrHPP, Innate Pharma, Marseilles, France) was able to vigorously expand Vg9Vd2 T cells owing a broad reactivity against tumor cell lines [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, cd T cell subsets recognize the non-classical MHC class I molecules T10/T22 [15], and an unknown ligand expressed by keratinocytes [16]. In humans, some Vd1 cd T cells recognize non-classical MHC class I molecules MICA and MICB, and Vc9Vd2 cd T cells have been reported to recognize self and bacterial phosphoantigens, and a complex formed between F1-ATP synthase and apolipoprotein A-1 [5,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, cd T cell subsets recognize the non-classical MHC class I molecules T10/T22 [15], and an unknown ligand expressed by keratinocytes [16]. In humans, some Vd1 cd T cells recognize non-classical MHC class I molecules MICA and MICB, and Vc9Vd2 cd T cells have been reported to recognize self and bacterial phosphoantigens, and a complex formed between F1-ATP synthase and apolipoprotein A-1 [5,[17][18][19][20].During mouse NK cell development, lineage markernegative bone marrow progenitors develop progressively into CD122 + NK1.1 -DX5 -committed NK progenitors, CD122 + NK1.1 + DX5 -immature NK cells and finally CD122 + NK1.1 + DX5 + mature NK cells, all of which can be found in the bone marrow. At the immature DX5 -stage, NK cells express multiple NK receptors including CD94/NKG2, NKG2D and NKp46, but are unable to perform granule-mediated cytotoxicity [21][22][23].…”
mentioning
confidence: 99%